Quality Prerequisites of Fruits for Storage and Marketing - Ahmad, Md Shamsher; Nayyer, Md Abu; Aftab, Ahmar; Nayak, Basant; Siddiqui, Md Wasim (Journal of Postharvest Technology, 2014)
Quality is a major component that attracts consumers of all ages. If the consumers like it, they are ready to pay a premium price. India is the second largest producer of fruits in the world. However, quality of the produce is not up to the world standard level. There may be many reasons for this, but one of the main reasons is lack of knowledge. Most producers are small and marginal farmers and they are not much aware about quality. Country’s current distribution system of fresh produce is also inefficient in maintaining quality in the long supply chain between producers and consumers. With the amendment in the policy of Agricultural Produce Market Committee, recently a few reputed companies entered into fruit business on small, medium, and large-scale. These firms increased quality bars of Indian fruits as only quality fruits are purchased and sold by these firms.